Rib Variation at Multiple Locations and Implications for Histological Age Estimation*. Issue 6 (4th August 2020) - Dominguez, Victoria M.; Harden, Angela L.; Wascher, Matthew; Agnew, Amanda M.
Abstract: Existing histological age estimation methods using the rib were developed mainly from the midshaft; however, in forensic practice, uncertainty of sampling location often arises due to fragmented or previously sampled ribs. The potential for error increases when sampling location is uncertain and utilizing a section beyond the midshaft (either anterior or posterior) may result in erroneous age estimates. Additionally, there is debate within the field regarding the minimum number of sections needed for accurate age estimation. The aim of this research is to determine the importance of the midshaft distinction for age‐at‐death assessment and the necessity of analyzing serial sections by evaluating histological variables at sampling locations along the length of the rib. Three seriated histological sections at three sampling locations (anterior, midshaft, and posterior) were obtained from sixth ribs of ten postmortem human subjects. Cortical area (Ct.Ar) and osteon population density (OPD) were collected from each section ( n = 90). Significant differences were determined in Ct.Ar between sampling locations, demonstrating the variation present along the length of the rib. A comparison of OPD at sampling locations revealed significant differences, suggesting that sampling site is critical to accurate age estimates. When sampling location is uncertain, a more anterior section should be taken. Analysis of serial sections within locations revealed no significant differences in OPD or Ct.Ar, supporting the practice of collecting data from one section for age estimation. While an age estimate can be achieved through the analysis of one section, best practice suggests reading two sections to capture intraindividual variation.